Calcium Transport in the Kidney and Disease Processes - Hanna, Ramy M.; Ahdoot, Rebecca S.; Kalantar-Zadeh, Kamyar; Ghobry, Lena; Kurtz, Ira (Frontiers in Endocrinology, 2022)
Calcium is a key ion involved in cardiac and skeletal muscle contractility, nerve function, and skeletal structure. Global calcium balance is affected by parathyroid hormone and vitamin D, and calcium is shuttled between the extracellular space and the bone matrix compartment dynamically. The kidney plays an important role in whole body calcium balance. Abnormalities in the kidney transport proteins alter the renal excretion of calcium. Various hormonal and regulatory pathways have evolved that regulate the renal handling of calcium to maintain the serum calcium within defined limits despite dynamic changes in dietary calcium intake. Dysregulation of renal calcium transport can occur pharmacologically, hormonally and via genetic mutations in key proteins in various nephron segments resulting in various diseases processes. This review focuses on the regulation transport of calcium in the nephron. Genetic diseases affecting the renal handling of calcium that can potentially lead to changes in the serum calcium concentration are reviewed.